Correção de apagamentos em rajadas utilizando códigos LDPC gerados pela composição de matrizes bases e pelos moviementos de matrizes circulantes - SILVA, Cássio André Sousa da (Universidade Federal do Pará, 2017)
This thesis proposed procedures for the construction of parity check matrices for encoding and decoding of LDPC codes in the recovery of deleted bits in Burst Erasure Channel. The parity check matrices are produced by concatenation of binary bases matrices juxtaposed by circulating matrices are easy to implement and lower randomness. The base arrays are developed from the foundations of algebra and geometry. To demonstrate the potential of the technique, we developed a number of simulations using low complexity encoding as well as the sum-product algorithm. Several LDPC codes (matrices) were generated and the results were compared with other approaches. We also present the outcomes of erasure recovery simulations that result from the transmission of an image through a noisy channel.